Acute Myocardial Injury in Association with Metformin Toxicity - Garg, Ashish; Sánchez-Solano, Nataly Judith; Gorla, Sudheer R.; Swaminathan, Sethuraman (Journal of Pediatric Intensive Care, 2018)
Metformin is one of the most commonly used oral hypoglycemic agents in the treatment of type 2 diabetes mellitus. Toxicity related to accidental or intentional ingestion of metformin is well reported in the pediatric literature. We report a case of transient acute myocardial injury documented by biochemical and electrophysiological evidences in an adolescent male who presented with intentional ingestion of a large dose of metformin. To our knowledge, this is the first such case of documented reversible myocardial injury in relation to metformin toxicity to be reported in the pediatric literature.
Keywords: metformin toxicity; lactic acidosis; myocardial injury